2007
DOI: 10.1577/t06-262.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Body Condition Indices and Proximate Composition in Adult Walleyes

Abstract: Relationships between indices of condition and measures of proximate body composition were examined among and within nine populations of mature walleyes Sander vitreus that varied widely in growth rate and lipid status. Body condition, measured as the residuals from mass versus length regressions, was negatively related to mean water content and positively related to mean lipid content among populations. When the roles of water and lipid content were examined simultaneously within populations, most of the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 35 publications
1
54
0
Order By: Relevance
“…Round goby collected from contaminated areas often have demonstrated ventral fin damage or erosion ; this study), but fish with eroded fins did not explore or disperse differently in a novel environment than fish with normal fins. Round goby from sites of low and high contamination were in similar body condition; condition reflects body composition and energetic levels (Kaufman et al 2007) and can be used as a contaminant biomarker (Schlenk et al 2008). Other physiological mechanisms, such as neurotoxic effects, chronic stress, or endocrine disruption may have been the proximate cause of the reduced activity here observed here, but these factors have yet to be explored in detail in this system.…”
Section: Discussionmentioning
confidence: 99%
“…Round goby collected from contaminated areas often have demonstrated ventral fin damage or erosion ; this study), but fish with eroded fins did not explore or disperse differently in a novel environment than fish with normal fins. Round goby from sites of low and high contamination were in similar body condition; condition reflects body composition and energetic levels (Kaufman et al 2007) and can be used as a contaminant biomarker (Schlenk et al 2008). Other physiological mechanisms, such as neurotoxic effects, chronic stress, or endocrine disruption may have been the proximate cause of the reduced activity here observed here, but these factors have yet to be explored in detail in this system.…”
Section: Discussionmentioning
confidence: 99%
“…Where autocorrelation was significant, the appropriate autoregressive terms were included in the models prior to testing for temporal trends. Morphometric body condition was estimated for each fish as the residual from a log e mass vs. log e FL relationship (Kaufman et al, 2007) fitted to the full data set (both species, both sexes, and all regions and years combined). For the analyses of growth rate and age and size of maturation, we pooled data into five 5-year intervals (1979-1983, 1984-1988, 1989-1993, 1994-1998, and 1999-2003, each inclusive) to improve sample sizes.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Changes in food availability due to changes in population abundance, ecosystem productivity, or prey community composition are often accompanied by a response in growth rates or energetic status for many fish species, including both lake whitefish (Healey, 1980;Mills, 1985;Pothoven et al, 2001;Lumb et al, 2007;Hoyle et al, 2008;Rennie et al, 2009) and walleye (Chevalier, 1977;Jones et al, 1994;Craig et al, 1995;Colby and Baccante, 1996). In the current study, we used somatic lipid content as an index of energy storage, a variable that correlates well with morphometric condition in both species (Kaufman et al, 2007;Rennie and Verdon, 2008). We found that lake whitefish grew more slowly than walleye, but also increased in lipid concentration with age, whereas walleye grew faster but declined in lipid concentration with age, particularly for females.…”
Section: Discussionmentioning
confidence: 87%
“…The methods used for fish processing and tissue analyses have been described in detail previously for walleye (Kaufman et al, 2007;Moles et al, 2008), and an identical protocol was used for lake whitefish. Briefly, each individual was measured from the tip of the snout to the fork of the caudal fin (fork length (FL), ±1 mm), then weighed with (total mass, ±10 g wet) and without gonads (somatic mass, ±10 g wet).…”
Section: Fish Processing and Laboratory Analysesmentioning
confidence: 99%
See 1 more Smart Citation